O tutor virtual como formador: a matemática no curso de pedagogia a distância da UFSCar - Bertini, Luciane de Fatima (2013)
The making of this paper was motivated by an interest in issues concerning the formation of (future) elementary math teachers through distance education and, in a more specific way, the role tutors play in this learning mode. The question that led our investigation was: Which online tutors actions in subjects that involve mathematics in a distance Pedagogy course allow us to identify them as teachers educators? Our theory referential approached issues on the formation of teachers in Pedagogy through discussions over mathematical formation in these courses, over the tutor s role and over the peculiarities of distance education, mainly regarding collective teaching. All data were collected in the Pedagogy course through distance education at Universidade Federal de São Carlos, an affiliate institution to the Brazilian Open University System (Sistema Universidade Aberta do Brasil). The object of the study allowed us to perform a case study which aims to develop knowledge by focusing a specific case and is represented in this study by online tutors work organization. The data that compose this research are questionnaires answered by tutors and students, material that is available online, interviews given by tutors, documents and Brazilian legislation regarding distance education as well as documentation on the organization of the university s distance courses. The analysis of the data took aspects of content analysis into consideration and was performed in a qualitative method. The tutors that were part of the research performed actions that allowed us to identify them as teachers educators in different moments: when they respected specific characteristics of distance education, when they approached issues regarding mathematics content and its teaching and when they acted independently during the collective teaching process. Besides their involvement with students formation, tutors acted as educators when they got involved in their own formative process and had a reflexive view on their own performances, on the course and on the distance education of mathematics. Working conditions, the way the coordination team organized the tutors work and the way each educator conducted his work influenced the tutors performances. After conducting the analysis, it was possible to consider that the quality of a teacher formation distance course is closely related to online tutors work organization and to the possibility that he/she plays the role of a teachers educator. Therefore the aspects that enable this performance must be kept, amplified and qualified and the ones that make the practice difficult must be discussed and minimized.